DESLOCAMENTOS URBANOS E EXPERIÊNCIAS POSSÍVEIS DO PEDALAR - Mathias, Fernando Manteufel Fiorotti (2021)
When thinking about the city from contemporary urban dislocation, we explore three spatial propositions based on Doreen Massey (2008): space in its multiplicity, as a product of interrelations and in constant process. We treat contemporary dislocation as measured by reading from studies of mobility and acceleration, based on analyzes by theorists Marc Augé (2010), Paul Virilio (1993), Richard Sennett (2002), Byung-Chul Han (2017), Eduardo Marandola Jr. (2011) and Janice Caiafa (2002). From these investigations, we explore the city exposed as urban polyphony, otherness and postures that inhabit flows at a creative pace. They also fundamental and inspire our reflection on these themes Massimo Canevacci (2004), Janice Caiafa (2003; 2019), Suely Rolnik (2006), Walter Benjamin (2013; 2015), Francesco Careri (2013) and Paola Jacques Berenstein (2003), both for their considerations and for the translation of the Situationist International (IS) material. By using the philosopher Jorge Larrosa's guy-experience and experience approach, we locate the body that pedals to enter the field, according to the bases launched by Marc Augé (2009) on the pedaling movement, and supported by Leandro Carmelini (2016), which brings five theoretical elements to consider the micropolitics of pedaling, anchored in poststructuralist philosophy. As a result, we prepared an Experiences Notebook, composed of five experiences documented in narratives and illustrations in the city of Vitória-ES.